2023
DOI: 10.1021/acscatal.3c02045
|View full text |Cite
|
Sign up to set email alerts
|

Propylene Metathesis over Molybdenum Silicate Microspheres with Dispersed Active Sites

David Skoda,
Ran Zhu,
Barbora Hanulikova
et al.

Abstract: In this work, we demonstrate that amorphous and porous molybdenum silicate microspheres are highly active catalysts for heterogeneous propylene metathesis. Homogeneous molybdenum silicate microspheres and aluminum-doped molybdenum silicate microspheres were synthesized via a nonaqueous condensation of a hybrid molybdenum biphenyldicarboxylatebased precursor solution with (3-aminopropyl)triethoxysilane. The as-prepared hybrid metallosilicate products were calcined at 500 °C to obtain amorphous and porous molybd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(195 reference statements)
0
4
0
Order By: Relevance
“…The in situ diffuse reflectance FTIR (DRIFTS) spectra of the M 1.5 -KIT-6, Mo 2 /KIT-6, and Mo 2 /M 1.5 -KIT-6 catalysts obtained during temperature-programmed desorption (TPD) of adsorbed pyridine in flowing He (40 sccm) between 150 and 300 °C and ∼0.1 kPa pyridine are shown in Figures and S22. Both the support and the Mo-doped catalyst contain predominantly Lewis acid sites, as inferred from the strong peak at ∼1448 and 1608 cm –1 , respectively, with one additional band at 1595 cm –1 . , Interestingly, this latter band was more prominent and well resolved in the bare transition supports (M 1.5 -KIT-6) and its intensity decreased upon Mo incorporation with a simultaneous increase in the intensity of the vibrational band at 1608 cm –1 (Figure S22). Such an interaction could possibly be due to the presence of different strengths of electrophilic Lewis acid sites that are characteristic of transition metals (Groups IV and V).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The in situ diffuse reflectance FTIR (DRIFTS) spectra of the M 1.5 -KIT-6, Mo 2 /KIT-6, and Mo 2 /M 1.5 -KIT-6 catalysts obtained during temperature-programmed desorption (TPD) of adsorbed pyridine in flowing He (40 sccm) between 150 and 300 °C and ∼0.1 kPa pyridine are shown in Figures and S22. Both the support and the Mo-doped catalyst contain predominantly Lewis acid sites, as inferred from the strong peak at ∼1448 and 1608 cm –1 , respectively, with one additional band at 1595 cm –1 . , Interestingly, this latter band was more prominent and well resolved in the bare transition supports (M 1.5 -KIT-6) and its intensity decreased upon Mo incorporation with a simultaneous increase in the intensity of the vibrational band at 1608 cm –1 (Figure S22). Such an interaction could possibly be due to the presence of different strengths of electrophilic Lewis acid sites that are characteristic of transition metals (Groups IV and V).…”
Section: Resultsmentioning
confidence: 98%
“…The higher activity was attributed to an increased population of the isolated dioxo species (OMoO) in the precatalysts. Recently, Skoda et al reported that porous molybdenum silicate nanospheres show 2-fold greater propylene metathesis activity compared to supported MoO x prepared by incipient wetness technique . The higher activity is attributed to increased dispersion of MoO x species.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the fact that a higher temperature is required to generate the metathesis active sites in the WO x /SiO 2 system, compared to the MoO x /SiO 2 catalyst. 4,7,8,14,15,21,22,76,77 The only exception is silanol-assisted activation of the M(IV) species (M = Mo, W) through the M(VI) hydride species. This mechanism is more favored for the tungsten system since W hydrides are more stable than Mo hydrides.…”
Section: Formation Of W(vi)mentioning
confidence: 99%
“…This catalyst, comprising mono-molybdates, poly-molybdates, and MoO3 crystalline clusters, represents typical industrial supported catalysts, as reported in prior literature. 19 The kinetics were measured under differential conditions, free from mass and heat transport limitations (Supplementary Eq. S1-S4).…”
Section: Kinetics Of Self-and Cross-metathesis On Moox-somcmentioning
confidence: 99%